Using electrospray ionisation mass spectrometry as a synthesis-targeting technique - An update on the chemistry of the platinum chalcogenide dimers [Pt2(μ2-E)2(PPh3)4] (E = S, Se) - Henderson, W. (2014)
10.1016/j.ica.2013.10.021